2016
DOI: 10.1039/c6cc01813k
|View full text |Cite
|
Sign up to set email alerts
|

bcTol: a highly water-soluble biradical for efficient dynamic nuclear polarization of biomolecules

Abstract: Dynamic nuclear polarization (DNP) is an efficient method to overcome the inherent low sensitivity of magic-angle spinning (MAS) solid-state NMR. We report a new polarizing agent (), designed for biological applications, that yielded an enhancement value of 244 in a microcrystalline SH3 domain sample at 110 K.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
71
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 58 publications
(74 citation statements)
references
References 38 publications
(5 reference statements)
0
71
0
Order By: Relevance
“…Synthesis of bcTol‐M started with the protected spirocyclohexanolyl nitroxide 1 , which was used for the synthesis of bcTol . Reductive amination of 1 with methylamine gave amino methyl derivative 2 in good yields.…”
Section: Resultsmentioning
confidence: 99%
“…Synthesis of bcTol‐M started with the protected spirocyclohexanolyl nitroxide 1 , which was used for the synthesis of bcTol . Reductive amination of 1 with methylamine gave amino methyl derivative 2 in good yields.…”
Section: Resultsmentioning
confidence: 99%
“…Enhancements, typically defined as the intensity of the NMR signal with microwaves on vs. microwaves off (I on /I off ), can practically range from minimal (i.e., no enhancement) to 515 on model compounds [41,45,46]. Counteracting this enhancement are detrimental effects of the sample conditions typically used for the DNP experiment, and thus this definition of enhancement is not a complete figure of merit.…”
Section: Introduction: Dnp Broadens the Horizons Of Solid State Nmrmentioning
confidence: 99%
“…Generally,a ny condition in which the g yy tensorc omponents of both radicals are perpendicular to one anotheri s expectedt oh ave near-optimal DNP performance. [30,33,34] Notably,i th as also been demonstrated that the TEKPola nd AMUPol biradicalsa re capable of yieldinge nhancement factors of upt o5 15 and 363 at 100 K, respectively,i n standard solutions that are doped with sapphire crystals. Lastly, the calculations showed that the electron T 1e value should be near 500 mst oy ield optimal performance.…”
Section: Introductionmentioning
confidence: 96%